(untitled) (Research, Society and Development, 2021)
This study aimed to develop a tapioca-flour-based dessert bar flavored with passion fruit pulp using a factorial design and response surface methodology. A 22 central composite rotatable design was adopted in which the independent variables were passion fruit pulp concentration (11%, 15%, 25%, 35% and 39%) and saccharose concentration (33%, 35%, 40%, 45% and 47%). The response variables assessed were sensory attributes of color, aroma, flavor, sweetness, texture, overall impression, and intent to purchase. The experimental design allowed optimizing the formulation of the dessert bar (11% passion fruit pulp, 40% saccharose, and 49% tapioca flour), which suggests response surfaces may be useful in product development based on sensory responses. The optimized formulation showed averages above 7 for the sensory attributes color, aroma, flavor, sweetness, texture and overall impression, which corresponded to acceptance rates above 84%. The dessert bar is a novel product of simple manufacture and low investment cost. It has high energy value and low risk of spoilage by microorganisms. It is also free of gluten, additives, and technology adjuvants.